Childhood and Disability in Brazil: A History of Blindness and Silencing - Cristina Borges de Oliveira (Arizona State University, 2011)
This article is a continuation of research involving inclusive educational policies, conceptions and transmission concerning childhood and the disabled child in Brazilian physical education academic production. The aim is to understand the history of childhood in Brazil, from the colonial period to the Republic and the role of government and civil society in relation to problems in the lives of children, specifically those with disabilities, in the history of Brazilian educational policies. Bibliographic and documentary research methods were used and the conclusion was reached that the history of childhood in Brazil has been marked by abandonment and disrespect. From total anonymity in the first centuries to our days, when the child is recognized as a citizen with rights and obligations, the idea of institutional and social care for children with disabilities has been given mere lip service.